Understanding the responses of deep convective clouds to a changing thermodynamic environment. - Leong, Marieanne Christie (2018)
Deep convective clouds play a key role in regulating the Earth’s water and energy cycles and are therefore an important component of the Earth’s climate system. Much work has been done on investigating factors such as how aerosols affect these clouds but much less emphasis has been on how the future changes in thermodynamic structure of the atmosphere will affect these clouds. It is vitally important to know how clouds will respond to these changed thermodynamic conditions.